The Role of Brand Image, Promotion, Price there is Trust, and Purchasing Decisions towards the Loyalty of Private Label Products of the traditional retail industry in Nunukan North Kalimantan - Mardiana, Mardiana; Nuryakin , Nuryakin (Riviera Publishing, 2022)
The purpose of this research is to examine, the effect of brand image, promotion, and price on trust, and purchasing decisions, the effect of trust on purchasing decisions, and customer loyalty, and the effect of purchasing decisions on loyalty. In this study, private-label brands in the retail industry in Yogyakarta are objects and the people of Yogyakarta are subjects with the minimum criteria for purchasing private labels three times. The sample is 272 respondents. The analytical tool used is SEM (Structural Equation Modeling) which is operated through the AMOS program. Sampling was carried out using a multistage random sampling technique. Furthermore, data collection is carried out by distributing questionnaires through a google form. The SEM method used in this study is the estimation of maximum probability and is used as a one-step approach in modeling the SEM approach. Descriptive statistical analysis and Cronbach’s alpha were performed with SPSS 21. SEM analysis was performed using the AMOS program. These results indicate that there is a positive and significant influence between Brand Image, Promotion, and Price on Trust and Purchase decisions. Trust has a positive and significant effect on Purchase Decisions and Loyalty, Purchase Decisions have a positive and significant effect on customer loyalty.